A Meta-Analysis of Endoscopic vs. Microscopic Transsphenoidal Surgery for Non-functioning and Functioning Pituitary Adenomas: Comparisons of Efficacy and Safety - Guo, Shengfu; Wang, Zidong; Kang, Xiaokui; Xin, Wenqiang; Li, Xin (Frontiers in Neurology, 2021)
Background: Although microscopic (MTSS) and endoscopic transsphenoidal surgery (ETSS) are both effective approaches for treating non-functioning pituitary adenomas (NFPA) and functioning pituitary adenomas (FPA), the consensus remains unidentified on whether there are differences in the risk of postoperative complications between the two surgical approaches. Method: A meta-analysis of the study of MTSS vs. ETSS for NFPA and FPA was conducted by searching the electronic databases of PubMed, Cochrane Library, and EMBASE, from the date of establishment of electronic databases to September 2020 based on the PRISMA guidelines. Results: In this study, a total of 16 studies were selected, hailing from Belgium, the USA, India, Finland, France, Korea, Spain, China, and Canada. We enrolled 1003 patients in the ETSS and 992 patients in the MTSS group. In patients with NFPA, the ETSS group was related to a higher incidence of post-operative gross-total resection (GTR). (OR = 1.655, 95% CI 1.131–2.421, P = 0.010). In participants with FPA, the results illustrated that the ETSS group had higher rates of visual improvement (OR = 2.461, 95% CI 1.109–5.459) and gross-total resection (OR = 2.033, 95% CI 1.335–3.096), as well as lower meningitis rates (OR = 0.195, 95% CI 0.041–1.923). In participants with acromegaly, no significant difference was shown in the postoperative complications. Conclusion: Based on current evidence, participants with NFPA treated by endoscopy were related to higher rates of GTR; patients with FPA treated by ETSS were related to higher rates of visual improvement and GTR, as well as a lower rates of meningitis.